Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper examines the selected issues related to the economy of Denmark: divergence in house prices, house prices in Denmark's cities, macroprudential policies, and product market reform and firm productivity. Recent house price developments in Denmark have been characterized by a growing divergence between different parts of the country, with big cities experiencing much more rapid price increases than other parts. House price booms and busts in Denmark, like in many other countries, are a big-city phenomenon. Macroprudential policies can help contain risks for households, the financial system, and the broader economy, but they should be carefully calibrated to avoid an undue drag on growth.